Johannes Gutenberg : INVENTOR AND CRAFTSMAN - Boone, Mary, 1963-; Butzer, Anna; Nuytten, Bobbie (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
Johannes Gutenberg wasn't just an inventor. He was also a goldsmith, printer, and publisher. Discover how Johannes found a way to bring information to people near and far.
Includes index.
Bibliography : page 23
Interest age level: Ages 6-9.
Keywords: Gutenberg, Johann, -- Juvenile literature -- 1397?-1468; Inventors -- Juvenile literature -- Biography -- Germany; Printers -- Juvenile literature -- Biography -- Germany